Novel treatment with double scope technique for disconnected pancreatic duct syndrome with external pancreatic fistula - Singla, Vikas; Gupta, Pankaj Kumar; Singh, Pankaj; Bopanna, Sawan; Shawl, Muzaffer Rashid; Soni, Harish; Goel, Akash; Madan, Kaushal; Garg, Pallavi; Bhargava, Richa (Endoscopy International Open, 2024)
Background and study aims External pancreatic fistula in association with disconnected pancreatic duct syndrome is a common sequelae of the percutaneous step-up approach for infected pancreatic necrosis and is associated with significant morbidity. The present study aimed to report the initial outcome of a novel technique of two-scope guided tractogastrostomy for management of this condition.Patients and methods The present study was a retrospective analysis of data from patients with external pancreatic fistula and disconnected pancreatic duct syndrome, who underwent two-scope-guided tractogastrostomy. All the patients had a 24F or larger drain placed in the left retroperitoneum. Transgastric echo endoscopy and sinus tract endoscopy were performed simultaneously to place a stent between the gastric lumen and the sinus tract. Technical success was defined as placement of the stent between the tract and the stomach. Clinical success was defined as successful removal of the percutaneous drain without the occurrence of pancreatic fluid collection, ascites, external fistula, or another intervention 12 weeks after the procedure.Results Three patients underwent two scope-guided tractogastrostomy. Technical and clinical success were achieved in all the patients. No procedure-related side effects or recurrence occurred in any of the patients.Conclusions Two-scope-guided tractogastrostomy for treatment of external pancreatic fistula due to disconnected pancreatic duct syndrome is a feasible technique and can be further evaluated.
Keywords: Pancreas; Endoscopic ultrasonography; Intervention EUS; Pancreatobiliary (ERCP/PTCD); MRCP topics